2011
DOI: 10.1021/jm200906r
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Analysis of Muraymycin Analogues: A Guide to the Design of MraY Inhibitors

Abstract: The systematic structure-activity relationship (SAR) of the muraymycins (MRYs) using an Ugi four-component reaction (U4CR) was investigated. The impact of the lipophilic substituent on antibacterial activity was significant, and the analogues 8 and 9 having a lipophilic side chain exhibited good activity against a range of Gram-positive bacterial pathogens, including MRSA and VRE. Further investigation of compounds 8 and 9 revealed these analogues to be selective inhibitors of the MraY transferase and nontoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
103
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(115 citation statements)
references
References 69 publications
5
103
0
7
Order By: Relevance
“…In contrast, the muraymycin analogues noted above were highly selective for MraY inhibition over E. coli WecA [23]. The action of CPZEN-45 will prompt further interest in the selective inhibition of WecA and TagO.…”
Section: Nucleoside Natural Product Inhibitors Of Mray and Related Enmentioning
confidence: 94%
See 1 more Smart Citation
“…In contrast, the muraymycin analogues noted above were highly selective for MraY inhibition over E. coli WecA [23]. The action of CPZEN-45 will prompt further interest in the selective inhibition of WecA and TagO.…”
Section: Nucleoside Natural Product Inhibitors Of Mray and Related Enmentioning
confidence: 94%
“…In recent years several studies have used synthetic chemistry to access analogues with higher chemical stability or altered antibacterial spectrum. with muraymycin D2 IC50 0.01 µM) and antibacterial activity [22], and that the cyclic epicapreomycidine amino acid could be replaced by arginine, lysine or ornithine residues [23]. Using L-arginine in place of epicapreomycidine, Takeoka have further shown that the Cterminal amino acid can be removed while retaining full MraY inhibition activity, and enhanced antimicrobial activity against strains of Pseudomonas, and that an analogue containing two L-arginine residues shows MIC 4-8 µg/ml against Pseudomonas strains [24].…”
Section: Nucleoside Natural Product Inhibitors Of Mray and Related Enmentioning
confidence: 99%
“…44) Although inhibitory activity of epi-MRY D2 (32) was weakened, it still showed potent inhibitory activity (IC 50 0.09 µM, K i 49 nM). As for the mode of inhibition, these compounds present a common behaviour with respect to the substrates of MraY: they were all competitive and noncompetitive inhibitors toward the nucleotide and the lipid substrates, respectively.…”
Section: Medicinal Chemistry Of Muraymycinsmentioning
confidence: 98%
“…A major difference between both modes of interaction is the positioning of The effect of introducing a hydrophobic moiety on an aminoribosyl scaffold has already been reported. 34,35 On the one hand, Dini et al 34 reported an interesting SAR study of aminoribosyl uridine derivatives lacking the hydroxyl group at C-3′ and bearing various substituents at C-5′. Their study showed that the introduction of a hydrophobic chain at C-5′ led to a five-to ten-fold increase of in vitro potency compared to that of the parent compound.…”
Section: Molecular Modelingmentioning
confidence: 99%
“…These results are in good agreement with a positioning of the inhibitors according to the mode A suggested by our docking experiments. On the other hand, Matsuda et al 35 reported the synthesis of muraymycins analogues with an elaborate urea-dipeptide motif introduced on an amino acid at the C-5′ position of an aminoribosyl uridine scaffold. Biological evaluation of several analogs differing in the hydrophobic chain introduced on this urea-dipeptide was also reported and showed that the presence of a long hydrophobic chain decreased the inhibitory activity by a factor 30, while the antibacterial activity was improved due to a better membrane penetration.…”
Section: Molecular Modelingmentioning
confidence: 99%